2020
DOI: 10.1016/j.acra.2019.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac CT in the Preoperative Diagnostics of Neonates with Congenital Heart Disease: Radiation Dose Optimization by Omitting Test Bolus or Bolus Tracking

Abstract: Rationale and Objectives: Congenital heart diseases (CHD) belong to the leading causes of infant mortality worldwide. Prognostic improvements result from multimodal therapy strategies leading to an increased demand for noninvasive imaging. The aim of the study was to further optimize cardiac CT radiation dose by omitting the test bolus or bolus tracking scan, which can have a relevant share of radiation exposure, especially in neonates. Materials and Methods: This retrospective study included 25 neonates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…We reported a mean effective radiation dose of 0.39 ± 1.2. Table 6 displays previously published radiation doses of CCT studies in young infants applying different ECG-gating techniques, using different scanners, and contrast-timing techniques in the context of our study dose (15,16,18,2530). Our study’s suggested protocol achieved a low dose of radiation compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We reported a mean effective radiation dose of 0.39 ± 1.2. Table 6 displays previously published radiation doses of CCT studies in young infants applying different ECG-gating techniques, using different scanners, and contrast-timing techniques in the context of our study dose (15,16,18,2530). Our study’s suggested protocol achieved a low dose of radiation compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…For the adjustment of contrast-opacification timing, Goo and Yang (31) (24). Lastly, Schindler et al tried a scan delay of 8 s, aiming to opacify the pulmonary circulation or the right heart side and 12 s for the opacification of the aorta and the left heart side with some variability according to the heart defect and its associated hemodynamics (15). In our study, we used an estimated scan delay of 4 s, optimized to opacify the right heart side or 8 s for the opacification of the left side or aorta added to the calculated contrast injection time that was not fixed and could be adjusted according to the size of the heart chamber and the expected associated hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tube modulation, kV modulation in smaller size and younger patients, z-axis overscan, scan length limitation, use of iterative reconstruction algorithms, use of dual energy (particularly important for contrast enhanced exams in patients with renal function problems), use of machine learning and artificial intelligence algorithms [22,[48][49][50][51][52][53][54]. Cardiac high-pitch CT angiography of neonates with congenital heart diseases can be performed safely and with dose reduction without additional test bolus or bolus tracking scans [55]. Demb et al 2017 provided a comprehensive optimization step approach by analyzing 158,274 diagnostic CT scans and concluding that by reviewing institutional doses and sharing dose-optimization best practices, lower radiation doses for chest and abdominal CT, and more consistent doses for head CT were reported [56].…”
Section: Ctmentioning
confidence: 99%